Age estimation in forensic investigations using tooth cementum annulations and pulp to tooth area ratio - Athira, C P; Murthy, Sarvani; Naveen Kumar, R K; Niveditha; Indu Sundaram, T S; Jose, Jithin (Journal of Indian Academy of Forensic Medicine, 2021)
Forensic age estimation is beneficial in the process of identification of deceased in mass disasters and in determining age for social benefits, license and legal requirements. This study aims to compare two methods of age estimation; the tooth cementum annulations (TCA), and, pulp to tooth area ratio (PTR), in terms of reliability and correlation with actual age. Mandibular first premolar teeth which were used for the estimation of age using cementum annulations, were obtained from thirty patients undergoing therapeutic extraction for orthodontic treatment. For the same patients mandibular canine and premolar radiographs were also obtained with prior informed consent and were employed for age estimation using pulp to tooth area ratio. Mandibular first premolar teeth were sectioned for visualization of cemental annulations using phase contrast microscope. Number of TCA was added to the average age of eruption to estimate the age of individual. Mandibular canine and first premolar radiographs were taken using paralleling technique and PTR was estimated using Autocad 2007 software. TCA using phase contrast microscopy was found to be a highly reliable method for age estimation in comparison to PTR (p=0.000). When all the parameters used in the study were combined by multiple regression analysis, highest accuracy of age estimation with least standard deviation of 1.86 years was obtained. Age estimation from tooth cementum annulations is more accurate when compared with pulp to tooth area ratio. The combination of different methods will provide more reliability in age estimation as compared to relying upon a single method.